A Project-based learning approach:Literature and development of critical thinking through The Bluest Eye and multimodal texts in the EFL classroom - Olid-Román, María Rosa (My University, 2023)
In the context of literature in the EFL classroom, this thesis aims to present an intervention proposal for students of the first Baccalaureate to promote critical thinking skills and apply critical literacy through literary texts. In order to approach this objective, representative examples from the novel The Bluest Eye (Morrison, 1970) and the poem The King of Harlem (Lorca, 1929) will be analysed together with multimodal texts. A literature review related to the topic will be discussed, focusing on the development of critical thinking skills via intensive and extensive reading. Evidence for and against literature will be explored. There will be a section devoted to PBL methodology by linking it to literature. The theoretical knowledge previously considered will be presented in the planification of a project contextualized according to the legislative framework of Andalusia (Spain). Lastly, conclusions, limitations and further research are considered.
Keywords: literature; critical thinking; EFL; PBL; multimodal texts; Máster Universitario en Enseñanza de Inglés como Lengua Extranjera